THE CONDITIONS OF BAITUL MAAL WAT TAMWIL (BMT) IN INDONESIA: A LITERATURE REVIEW - Alvien Nur Amalia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2022)
The purpose of this research is to analyze the condition of BMT, is an Islamic microfinance institution in Indonesia, based on a literature review using SWOT analysis. Based on the SWOT analysis BMT’s strengths, weaknesses, opportunities, and threats will be mapped through four types of strategies, namely aggressive, competitive, conservative and defensive strategies. The results indicate that based on the analysis of aggressive strategies, BMT is a community-based agency that has an opportunity to capture the market; BMT can use the ZISWAF fund in cooperation with charity institutions. Based on the analysis of competitive strategies, BMT competition with conventional micro institutions can be solved by Islamic economic socialization about the prohibition of usury; competition with Islamic banks that have a microfinance program can be solved with the distribution of business; BMT sustainability issues can be overcome by strengthening the regulation, supervision, infrastructure, human resources, and capital. From the conservative strategies, BMT has limitations in terms of capital, human resources, and marketing strategies. This problem can be overcome through their linkage with Islamic Banks and companies, using CSR and low-cost funds from Islamic Banks. Other opportunities are the transfer of knowledge about finance, managerial expertise, as well as the right marketing strategy. In addition, a lack of oversight in BMT can be solved by maximizing the role of associations and agents of BMT. Meanwhile, from the defensive strategies, fundamental reform of government is required to develop BMT’s rules, oversight, feasibility measurement and clear level of health.